2019
DOI: 10.3847/2041-8213/ab276d
|View full text |Cite
|
Sign up to set email alerts
|

CO Detected in CI Tau b: Hot Start Implied by Planet Mass and MK

Abstract: We acquired high resolution IR spectra of CI Tau, the host star of one of the few young planet candidates amenable to direct spectroscopic detection. We confirm the planet's existence with a direct detection of CO in the planet's atmosphere. We also calculate a mass of 11.6 M J based on the amplitude of its radial velocity variations. We estimate its flux contrast with its host star to get an absolute magnitude estimate for the planet of 8.17 in the K band. This magnitude implies the planet formed via a "hot s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 50 publications
6
28
1
Order By: Relevance
“…This agreement further supports our luminosity estimate and the associated radius value, and may even suggest that both are still slightly underestimated; given the reported values of v sin i and P rot , a lower luminosity and a smaller radius would indeed imply that the inclination of the star significantly differs from that of the disc. This places the co-rotation radius of CI Tau (i.e., the radius at which the Keplerian orbital period equals the stellar rotation) at a distance of r cor = 0.082 ± 0.001 au or 8.8 ± 1.3 R ⋆ from the centre of the star, thereby setting the co-rotation velocity at 99 ± 1 km s −1 and its line-of-sight projection at 76 ± 5 km s −1 for a disc inclination of 50 ± 4 • (Guilloteau et al 2014;Clarke et al 2018), consistent with the RV semi-amplitude of the CO signature recently reported (equal to 77 km s −1 , Flagg et al 2019).…”
Section: Evolutionary Status Of CI Tausupporting
confidence: 89%
See 1 more Smart Citation
“…This agreement further supports our luminosity estimate and the associated radius value, and may even suggest that both are still slightly underestimated; given the reported values of v sin i and P rot , a lower luminosity and a smaller radius would indeed imply that the inclination of the star significantly differs from that of the disc. This places the co-rotation radius of CI Tau (i.e., the radius at which the Keplerian orbital period equals the stellar rotation) at a distance of r cor = 0.082 ± 0.001 au or 8.8 ± 1.3 R ⋆ from the centre of the star, thereby setting the co-rotation velocity at 99 ± 1 km s −1 and its line-of-sight projection at 76 ± 5 km s −1 for a disc inclination of 50 ± 4 • (Guilloteau et al 2014;Clarke et al 2018), consistent with the RV semi-amplitude of the CO signature recently reported (equal to 77 km s −1 , Flagg et al 2019).…”
Section: Evolutionary Status Of CI Tausupporting
confidence: 89%
“…Among the handful of cTTSs identified for observations within the MaPP and MaTYSSE Large Programmes carried out at Canada-France-Hawaii Telescope (CFHT) with the ESPaDOnS spectropolarimeter, CI Tau, reported to potentially host a close-in giant planet (Johns-Krull et al 2016;Biddle et al 2018;Flagg et al 2019), is thus especially interesting for tomographic studies based on spectropolarimetric monitoring. In this paper, we present ESPaDOnS observations of CI Tau collected from mid December 2016 to mid February 2017; following a short review of the evolutionary status of this cTTS, we analyze our new data in terms of the large-scale magnetic topologies that the newborn star hosts, and of the accretion patterns that the star-disc interactions trigger.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the three planets at tens of AU separations analysed here, it also hosts a very massive M p ≈ 12 M J hot Jupiter at separation of only ∼ 0.1 AU. The planet luminosity is consistent with the hot start models (Flagg et al 2019), potentially implying the planet was made by GI and migrated to its present location. Being as massive as it is, the planet should be migrating in the type II regime, with t mig2 ≈ M p / M * ∼ 3 × 10 5 yr…”
Section: Discussion Of the Paradox Of Youthsupporting
confidence: 78%
“…Separating the spectrum of the planet from the host star using this Doppler shift was first applied to detect absorption by atmospheric CO in the infrared transmission spectrum of HD 209458 b (Snellen et al 2010). Later efforts employed this technique to detect the thermal emission of both transiting and nontransiting hot Jupiters, resulting in detections of CO, H 2 O, CH 4 , and HCN (e.g., Brogi et al 2012Brogi et al , 2016Birkby et al 2013Birkby et al , 2017Lockwood et al 2014;Piskorz et al 2016;Hawker et al 2018;Cabot et al 2019;Guilluy et al 2019;Flagg et al 2019). The technique has also been applied at optical wavelengths to detect TiO in the dayside spectrum of WASP-33 b using the HDS/Subaru 6 instrument (Nugroho et al 2017) and atomic metal lines in the transmission spectrum of KELT-9 b (Hoeijmakers et al 2018a(Hoeijmakers et al , 2019 using HARPS-N/TNG and PEPSI/LBT 7 (Cauley et al 2019).…”
Section: Introductionmentioning
confidence: 99%